2003
DOI: 10.1096/fj.02-0796fje
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiac BNP expression associated with myocardial ischemia

Abstract: Congestive heart failure is accompanied by increased cardiac brain natriuretic peptide (BNP) gene expression with elevated plasma concentrations of BNP and its precursor, proBNP. We investigated if myocardial ischemia in the absence of overt heart failure may be another mechanism for increased myocardial BNP expression. The BNP expression was examined in hypoxic myocardium of patients undergoing coronary bypass grafting surgery, in patients with coronary artery disease and normal left ventricular function unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
207
0
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(228 citation statements)
references
References 25 publications
5
207
0
11
Order By: Relevance
“…Toth et al (25) have found evidence that tissue hypoxia alone triggers release of BNP in absence of LV dysfunction. These results were confirmed by a recent physiological study showing that ventricular BNP gene expression is up-regulated by myocardial hypoxia resulting in augmented plasma concentrations of BNP and NT-proBNP (26). The association of elevations of BNP with a greater severity and extent of ischemia may explain, atleast in part, the adverse clinical outcomes of such elevation.…”
Section: Discussionsupporting
confidence: 64%
“…Toth et al (25) have found evidence that tissue hypoxia alone triggers release of BNP in absence of LV dysfunction. These results were confirmed by a recent physiological study showing that ventricular BNP gene expression is up-regulated by myocardial hypoxia resulting in augmented plasma concentrations of BNP and NT-proBNP (26). The association of elevations of BNP with a greater severity and extent of ischemia may explain, atleast in part, the adverse clinical outcomes of such elevation.…”
Section: Discussionsupporting
confidence: 64%
“…Correlation analysis and stepwise regression analysis revealed that AVI was positively related to age, PP, SBP and BNP. Advanced age, increased PP and SBP are well documented risk factors for cardiovascular events (Darne et al 1989;Tokitsu et al 2015), while increased BNP level is a strong predictor of cardiac dysfunction (Goetze et al 2003;McLean et al 2003). In this sense, AVI may be an integrated embodiment of several indicators of cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Goetze demonstrated that myocardial ischemia in the absence of left ventricular dysfunction augments cardiac BNP gene expression and increases plasma NT-proBNP concentrations. Quantitative analysis of BNP mRNA in ventricular biopsies revealed close association of plasma NT-proBNP to BNP mRNA levels (22).…”
Section: Discussionmentioning
confidence: 98%